New Products Development through Customized Design Based on Customers' Needs. Part 2: Foot Pathology Manufacturing Parameters. (2016) - Deselnicu, Dana Corina; Vasilescu, Ana Maria; Mihai, Aura; Purcarea, Anca Alexandra; Militaru, Gheorghe
Abstract: The article presents the methodology and results of a fieldwork study conducted in order to obtain new customized footwear products designed based on elderly customers' needs evaluation. The outcomes of the study are presented in two articles. This second part outlines the results concerning foot pathologies constraints for the manufacturing of customized products for elderly people. Because of their foot deformities, if elderly people use mass footwear they have access to, they suffer from skin damage and other similar foot pathologies, which ultimately affect their general health and increase public health expenses. The research aimed at investigating the development of new footwear products considering the foot pathologies of elderly customers in Romania. The research used a consumer survey based on quantitative methodology using a multi-section investigation instrument to generate an inventory of elderly consumers' foot pathology needs. The conclusions clearly highlight the strong need for the development of new customized products.